Pengembangan Konten Pembelajaran Audio Visual untuk Materi Jaringan Nirkabel melalui Fitur Reels Instagram pada Jurusan Teknik Komputer Jaringan SMK Negeri 4 Malang - Gayus Reinaldy Manere Sulli Danan; Hanifah Muslimah Az-Zahra; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
The purpose of this project was to provide instructional materials for Wireless Networks using audio-visual formats for the Department of Computer and Network Engineering at SMK Negeri 4 Malang. Follow up on issues with the Introduction to Schooling Field II observation findings at the Department of Computer and Network Engineering at SMK Negeri 4 Malang. The research & development (R&D) approach was employed in this investigation. The Department of Network Computer Engineering at SMK Negeri 4 in Malang City served as the research site. The design is carried out utilizing the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) instructional approach. Utilizing the steps of analysis of footage that has been approved for usage as audio-visual production using the Instagram reels application. It will result from the current phases and methods in: Material Analysis and Validation, Storyboards are used as a kind of design, followed by manufacturing or development phases that provide media validation, distribution of produced audio-visuals to respondents, and evaluations that concentrate on development utilizing learners' interests. The degree of student interest in learning is the only criterion for the success of this development investigation. The success of product design is obtained from the achievement of the use of media which includes: (1) the suitability of aspects from material experts, audio-visual media experts. (2) well received by students of the Network Computer Engineering Department at SMK Negeri 4 Malang (3) as a learning medium that supports school learning. The results of this study indicate the creation of learning media products in the form of Short Learning Videos with the Instagram Reels Feature which can help deliver material on Wireless Networking subjects and support ongoing learning. Short learning videos can also become new teaching media that students are interested in, so that the learning development model with this learning video in the future can be recommended as a new innovation in learning.